Perceptions communautaires sur les services écosystémiques d’approvisionnement fournis par le peuplement ligneux de la Réserve de Biosphère du Ferlo (Sénégal) - Daouda Ngom; Mohamed M. Charahabil; Oumar Sarr; Amy Bakhoum; Léonard E. Akpo (VertigO)
The analysis of relations between local communities and their natural environment is more and more based on the concept of ecosystem services. Through surveys, interviews, informal discussions, measures and field observations, we studied the services provided by ecosystems to population in the Ferlo biosphere reserve. The flora identified by local communities is composed by 44 woody species belonging to 36 genera and 20 botanical families. These species listed contribute to the provision of six categories of ecosystem services supply by an informant consensus factor of more than 70%. In terms of importance of the percentage of use, the categories of ecosystem services supply listed are food (23.7%), medicines (20.3%), fodder (18.7%) the timber (16.3%), the energy wood (15.9%) and craft wood (5.3%). The species with the highest use values for all categories of services combined are Grewia bicolor Juss. (2.43), Pterocapus lucens Lepr. Ex Guill.α Perr (1.68), Combretum glutinosum Perr. ex DC (1.48), Guiera senegalensis J.F. Gmel (1.38), Ziziphus mauritiana Lam. (1.25), which is an indicator of high pressure use of these species.